Determination of the Qibla Direction of the Al-Mukarramah Mosque in Gampong Punge Jurong, Meuraxa District, Banda Aceh City - Ida Friatna; Riza Afrian Mustaqim; Erizaldi Putra (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2023)
One of the conditions for a valid prayer is facing the Qibla, Imam Syafi'i believes that people who can see the Ka'bah must face the 'Ainul Ka'bah as well as people who are far or outside Mecca must face 'Ainul Ka'bah based on their ijtihad with instructions from the sun, stars, mountains, moon, and others that can be used as a Qibla direction. Many mosques in the city of Banda Aceh do not face the Kaaba, this is based on using Google Earth, from several mosques that are off the beaten path, the Al-Mukarramah Mosque has such a large deviance that it faces the African continent. The research question for this thesis is how to determine the Qibla direction at Al-Mukarramah Mosque, Gampong Punge Jurong, Meuraxa District, Banda Aceh City and how accurate the Qibla direction at Al-Mukarramah Mosque, Gampong Punge Jurong, Meuraxa District, Banda Aceh City. In this study the authors used a qualitative approach research method, a type of Field Research (field research), and used a qualitative descriptive analysis method. describe and analyze the method of determining the Qibla direction of the Al-Mukarramah Mosque then verify the results of Qibla accuracy. The results of this study concluded that first, the method of determining the Qibla direction of the Al-Mukarramah Mosque in Gampong Punge Jurong, Meuraxa District, Banda Aceh City was carried out in two ways: 1) Rashdul Qibla, when the Al-Mukarrmah Mosque was about to be built in 1999 by the Imam of Gampong Punge Jurong during the that, 2) Kompas, carried out in 2018 this happened when the Aceh MPU fatwa No. 3 of 2018 concerning the determination of the Qibla direction. Second, test the accuracy of the Qibla direction of the Al-Mukarramah Mosque by using the Mizwala Qibla Finder, Rubu' Mujayyab, Protractor, and Google Earth that the Qibla direction of the mosque does not face the Ka’bah so it has a slope with the position of the mosque building by 15° to the north and results via visual google earth The building of the Al-Mukarramah mosque faces the African continent.